VHPKQHR peptide modified magnetic mesoporous nanoparticles for MRI detection of atherosclerosis lesions - Wan Xu; Shuihua Zhang; Quan Zhou; Wenli Chen (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Mortality attributable to atherosclerosis can be reduced significantly with timely diagnosis and treatment. It is meaningful to find a proper way to diagnose and prevent the progression of atherosclerosis. Vascular cell adhesion molecule-1 (VCAM-1) expressed by endothelial cells is a prominent marker of atherosclerotic plaques. There are a number of researches on VCAM-1 based probes for targeted imaging, but rarely on a system with both targeting and drug delivery. Here, we report a novel magnetic mesoporous silicon nanoparticle that is capable of drug delivery and targeting at atherosclerosis plaque. The nanoparticles were constructed using incorporated FITC (fluorescein isothiocyanate) and VHPKQHR peptide into Fe3O4@SiO2 (FITC-VHP-Fe3O4@SiO2). The FITC-VHP-Fe3O4@SiO2 nanoparticles showed great morphological characteristics, superior targeting ability, low toxicity and good biocompatibility in vitro and in vivo. The in vivo experiments showed that FITC-VHP-Fe3O4@SiO2 is a superior contrast agent of magnetic resonance imaging (MRI) for diagnosis of atherosclerosis plaques.